Supervisors Sharia Board Toward Financial Performance Sharia in Salatiga - Desi Trisnawati (ProBisnis : Jurnal Manajemen, 2022)
Objective of this study is test Board Supervisor Sharia affects the performance of Islamic financial institutions. supervisory Board Sharia in this study are: Size of the Sharia Supervisory Board, Total Meeting of the Sharia Supervisory Board, Attendance of the Sharia Supervisory Board in meetings, Background Behind Education Board Supervisor Sharia and Proportion Women on the Sharia Supervisory Board. Performance of Islamic financial institutions on this research refer to performance maqashid sharia. This research was conducted on 10 Islamic banks listed on the Exchange Indonesian Securities as a sample with the 2011-2015 research period. Testing influence Board Supervisor Sharia on performance institution finance sharia with use regression double. The results of the study show that the size of the Sharia Supervisory Board, Educational Background of the Sharia Supervisory Board and Proportion of Women on Board Supervisor Sharia influential on performance institution finance sharia in matter This performance maqashid sharia